KARAKTERISTIK KEPEMIMPINAN PENDIDIKAN ISLAM BERBASIS MASJID - M. Hidayat Ginanjar; Wartono . (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2018)
Leadership is the ideal of quality, both in terms of physical, mental, and intellectual.Maturity in terms ofthis aspect will help a leader in carrying out the task. Knowledgeand a wide perspective is the key in solving many problems that block or makesome breakthroughs for the success of the important task of a leader. Islamencourage every Muslim to have these three types of power. The strong and goodbelievers are well loved by Allah more than the weak believers, each has a virtue.For that, the vision and values of leadership comes from the ideal practices ofRasulullah peace be upon him (Shalallahu 'alaihi wa sallam) and the Companions, itis necessary and must continue to be extracted, distributed and socialized tobecome a strong issue in the stage of leadership in society. Therefore, a goodleadership is absolutely needed by the community, and of course the leaders areexpected to appear is a leader that has a nature or character laudable. That is, onthe side of truth, justice, has the nature of trust, a worthy model, simplicity,greatness of the soul, forgive person, and others who emphasize kindness for thepeople.One of the leadership Islamic education models is leadership based mosque,the mosque is a place where Muslims join together in routines worship, both(hablum minallah) (relationship between human and Allah) or (hablum minannas)(relationship between human and human). For Muslims, the mosque become theheart moorings, the port development and the life energy of Muslims. mosques alsofunction as institutions of education and knowledge of Islam. In addition, the mosqueis also a place that can be delivered candidates Islamic leaders in the future, asevidenced (applied) by Rasulullah peace be upon him (Shalallahu 'alaihi wa sallam),he built with the friends so that future generations be able to lead the best andpeople through developments that centred in mosque. People were educated inmosques in a shelter of the high Islamic society and give priority in deliberation forsolving problems. The mosque which was established on the basis of devotion toAllah will inure to the influence of education in human life. Thus, the mosque-basedleadership can bear a good leader, the leader of a people-oriented development, sothat it can be delivered to devotee individuals, able to lead and bring the nextgeneration achieve their hopes; establishing a believer for himself, family,community, nation and state.Keyword: Islamic Education, Leadership, Caracter, Mosqul Based.